Migration and wintering strategies of a Eurasian Stone-curlew ( Burhinus oedicnemus ) continental population, and their conservation implications - Emilie Dedeban; Pamela Lagrange; Alexandre Villers; Steve Augiron; Damien Chiron; Landry Boussac; Alexis Martineau; Willem Bouten; Vincent Bretagnolle (Avian Conservation and Ecology)
The Eurasian Stone-curlew ( Burhinus oedicnemus ) is a declining and threatened species, yet its migration and wintering strategies are little documented. Here, we used GPS trackers to collect accurate data on this species’ migration routes, stopovers, flight altitude, and speed, and identified the wintering sites of 32 individuals from a western European population tracked between 2012 and 2020. In a comparison between individuals, we found that they used strikingly different migratory strategies, showing variability in wintering sites (Portugal, Spain, Morocco, or Algeria), stopovers (number, location, and duration), and migratory routes, despite the fact that they all belonged to the same breeding population. We also compared individual variability in migratory routes, migration timing, and wintering home range size, and found medium to high repeatability for most parameters. In contrast to many other migrant waders, spring migration in this species was not found to be shorter in duration than autumn migration. Our results provide insights into potential threats that may affect this species in the near future away from its breeding grounds, such as habitat quality or habitat loss in wintering areas because Iberian or Moroccan agriculture is changing very rapidly because of drought.